2019
DOI: 10.1186/s12884-019-2673-0
|View full text |Cite
|
Sign up to set email alerts
|

Reducing intrapartum fetal deaths through low-dose high frequency clinical mentorship in a rural hospital in Western Kenya: a quasi-experimental study

Abstract: BackgroundIntrapartum fetal mortality can be prevented by quality emergency obstetrics and newborn care (EmONC) during pregnancy and childbirth. This study evaluated the effectiveness of a low-dose high-frequency onsite clinical mentorship in EmONC on the overall reduction in intrapartum fetal deaths in a busy hospital providing midwife-led maternity services in rural Kenya.MethodsA quasi-experimental (nonequivalent control group pretest – posttest) design in a midwife-led maternity care hospitals. Clinical me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 38 publications
2
26
0
1
Order By: Relevance
“…This con rms the cross-sectional study by [25], that among women who had ever given birth, the proportion of birth assisted by nurses/midwives had increased to about 79 percent. Also, the study by [34] conducted at Kenya con rms this nding. On the other hand, [24] concluded that the proportion of birth assisted by skilled birth attendants such as nurses/midwives has been low.…”
Section: Background Characteristics Of Respondentsmentioning
confidence: 55%
See 1 more Smart Citation
“…This con rms the cross-sectional study by [25], that among women who had ever given birth, the proportion of birth assisted by nurses/midwives had increased to about 79 percent. Also, the study by [34] conducted at Kenya con rms this nding. On the other hand, [24] concluded that the proportion of birth assisted by skilled birth attendants such as nurses/midwives has been low.…”
Section: Background Characteristics Of Respondentsmentioning
confidence: 55%
“…[31] concluded in multivariate regression that the odds of being assisted by nurses/midwives during delivery increased with mother's education. Also, a study in Kenya [34], Sierra Leon, Niger and Mali [12] and Ghana [13] established that women with higher education were more likely to use skilled attendant such as nurses/midwives.…”
Section: Background Characteristics Of Respondentsmentioning
confidence: 99%
“…10 Evidence suggests that post-training supportive supervision and mentorship are effective in strengthening learning processes, and improving provider motivation and clinical performance. [11][12][13] Studies conducted in Rwanda suggested that some of the reasons for low performance among healthcare providers can be traced through limited supervision and mentorship as well as insufficient support systems consistent with challenges reported in other similar settings. 8 14 15 Increasing the number of healthcare providers and training them to deliver quality care is a core component of health systems strengthening needed to achieve universal health coverage.…”
Section: Open Accessmentioning
confidence: 76%
“…A intervenção melhorou as competências da enfermeira/parteira para detectar, gerenciar e/ou encaminhar casos e/ou complicações de gravidez e parto, contribuindo para a redução das mortes fetais durante o parto. 20 Nesse contexto, pesquisa exploratório-descritiva de abordagem qualitativa, realizada em um município do interior do Rio Grande do Sul, que buscou conhecer a influência da atuação da Enfermagem entre os pais que vivenciam a morte do feto viável, não revelou influência significativa da assistência na vivência da morte fetal. Isso enfatizou a necessidade e importância do preparo profissional para atuar diante de situações extremas, como na perda fetal.…”
Section: Discussionunclassified